The Effectiveness and Safety of Adaptive Climbing in the Rehabilitation of Patients with Cerebral Palsy - Gennadii E. Sheiko; Anna N. Belova; Oksana V. Balandina; Natalia N. Rukina; Olga V. Vorobyova; Alexey N. Kuznetsov; Maxim A. Kavinov; Vyacheslav A. Orinchuk (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
The use of adaptive physical culture in the system of complex rehabilitation of patients with cerebral palsy (CP) is becoming more popular. Adaptive climbing (AC) is one of these types of physical culture and sports activities. Currently, there are not many data in the domestic and world literature devoted to the study of the AC use in the complex rehabilitation of patients with CP. Aim. Evaluation of the effectiveness and safety of AC in the rehabilitation of children and adolescents with spastic forms of CP in addition to conventional medical rehabilitation. Material and methods. The study included 30 patients aged from 5 to 18 years with spastic forms of CP who were allocated into one of two groups: the 1st group, the study group (n=15) - patients who underwent standard medical rehabilitation and AC classes; the 2nd group, the control group (n=15) - participants who received only medical rehabilitation. A comprehensive assessment of the rehabilitation measures effectiveness and safety was performed before the start of AC classes and after 3 months using clinical neurological and instrumental examinations, including biomechanical examination (electropodography, video analysis of walking and stabilography). Results. Group 1 patients showed a statistically significant improvement in general motor functions on the GMFM-88 scale (p=0,0001), a decrease in the level of spasticity on the мodified Ashworth scale (p=0,0051) and an improvement in manual abilities on the MACS scale (p=0,0431) 3 months after inclusion in the study. Positive dynamics in the form of an increase in the symmetry of step time (p=0,0063), step length (p=0,0083) and step velocity (p=0,0409) were noted according to the electropodographic study in the 1st group. A statistically significant increase in the range of motion in the hip (p=0,0038) and knee joints (p=0,0076) was detected in the 1st group according to video analysis of walking. There was no significant change in the indicators in the 2nd group, except for the severity of spasticity on the modified Ashworth scale (p=0,0180). A positive correlation was found between the indicators "step length" and " step velocity" (r=0,605, p=0,0168). A negative correlation was found between the "step velocity " indicator and the GMFCS score (r= - 0.832, p=0,0372). Only 2 adverse events were registered in the study group: acute respiratory viral infection and wrist injury during AC. Conclusion. AC, in addition to traditional methods of medical rehabilitation, leads to a decrease in spasticity, increased joint mobility and control of voluntary movements, improved maintenance of the body position, walking and precise hand movements, and also has a favorable safety profile. AC is an effective and safe motivating method of physical culture that can change the patient's view on traditional therapy.